Providing information sources domain for information seeking agent from organizing knowledge - Istiadi, Istiadi; Nugroho, Lukito Edi; Santosa, Paulus Insap (2014)
Abstract—This paper proposes a tracking mechanism to obtain the information sources that are stored on the personal knowledge organization which will be used to direct the search of information on the Internet by a software agent. Semantic representation of the organizer is viewed as a map of the information sources that are classified hierarchically based on the scopes of knowledge domains from the standpoint of the agent. The tracking mechanism by query will look for the information sources in the knowledge domains based on the same scope of a defined knowledge domain. This tracking will produce a list of information sources that will be followed to get the domain location as internet access preferences